2021
DOI: 10.1101/2021.11.12.21265796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission potential of vaccinated and unvaccinated persons infected with the SARS-CoV-2 Delta variant in a federal prison, July—August 2021

Abstract: BackgroundThe extent to which vaccinated persons who become infected with SARS-CoV-2 contribute to transmission is unclear. During a SARS-CoV-2 Delta variant outbreak among incarcerated persons with high vaccination rates in a federal prison, we assessed markers of viral shedding in vaccinated and unvaccinated persons.MethodsConsenting incarcerated persons with confirmed SARS-CoV-2 infection provided mid-turbinate nasal specimens daily for 10 consecutive days and reported symptom data via questionnaire. Real-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Longitudinal analyses of infectious viral shedding comparing vaccinated against unvaccinated individuals have shown conflicting outcomes, depending on the study population. In studies focused on university students and employees [26,29], the infectious period was shorter in vaccinated individuals. By contrast, in a federal prison population [29] the infectious period was similar in vaccinated and unvaccinated persons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal analyses of infectious viral shedding comparing vaccinated against unvaccinated individuals have shown conflicting outcomes, depending on the study population. In studies focused on university students and employees [26,29], the infectious period was shorter in vaccinated individuals. By contrast, in a federal prison population [29] the infectious period was similar in vaccinated and unvaccinated persons.…”
Section: Discussionmentioning
confidence: 99%
“…In studies focused on university students and employees [26,29], the infectious period was shorter in vaccinated individuals. By contrast, in a federal prison population [29] the infectious period was similar in vaccinated and unvaccinated persons. Recent data focused on the infectious virus titers over the first five days following symptom onset additionally indicate that vaccination, in the context of Delta circulation, leads to a reduction in the magnitude of infectious virus in early infection compared to unvaccinated Correlation between the maximum viral RNA level (N copies/ml) for a given participant and the infectious viral titer of that same nasal specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In studies focused on university students and employees 15 , the infectious period was shorter in vaccinated individuals. By contrast, in a federal prison population 29 the infectious period was similar in vaccinated and unvaccinated persons. Recent data focused on the infectious virus titers over the first five days following symptom onset additionally indicate that vaccination, in the context of Delta circulation, leads to a reduction in the magnitude of infectious virus in early infection compared to unvaccinated persons 30 .…”
Section: Discussionmentioning
confidence: 69%
“…However, contradictory evidence showed that the viral loads of breakthrough infections after full vaccination were similar with those in unvaccinated individuals (11, 12). More recently, a preprint study carried out in a prison demonstrated that there was no significant difference in the duration of RT-PCR positivity and the kinetics of Ct values between fully vaccinated participants and those not fully vaccinated (13).…”
Section: Introductionmentioning
confidence: 99%